CONTEMPORARY SECTARIANISM IN PAKISTAN: THE KURRAM DISTRICT PERSPECTIVE - Muzakir Khan; Muhammad Haroon; Kiramat Ullah; Prof. Dr. Ghulam Qasim Khan Marwat (`, 2025)
Sectarian violence in Kurram District, Pakistan, remains a significant challenge, with deep-rooted historical, political, and ideological causes. This paper explores the complex nature of sectarianism in the region, highlighting key factors such as tribal disputes, external influences, and the role of local governance mechanisms like tribal councils (jirgas) in mediating conflicts. While these councils have played a role in negotiating temporary ceasefires, their efforts have been ineffective in addressing the structural issues that fuel sectarian violence. The paper also examines the Pakistani government’s military interventions, which, although successful in addressing immediate threats, have been insufficient in preventing the recurrence of violence due to a lack of long-term strategic peacebuilding and legal reforms. In addition to state-led efforts, the paper discusses the impact of regional and cross-border militancy, particularly from Afghanistan, and the financing of extremist activities that further destabilize the district. The growing influence of sectarian militias, both local and foreign-backed, complicates efforts to establish lasting peace. Furthermore, the paper emphasizes the need for community-based approaches, such as strengthening interfaith dialogue and reconciliation mechanisms, to foster mutual understanding and trust between Sunni and Shia communities. Education and public awareness campaigns that promote religious tolerance and peace are proposed as essential tools to challenge sectarian narratives and prevent future violence. The role of the media in countering hate speech and fostering unity is also highlighted as a critical component in shaping public opinion and building a more inclusive society. Ultimately, the paper advocates for a holistic approach that combines local, national, and regional efforts to address the root causes of sectarianism, promote reconciliation, and ensure the long-term stability of Kurram District and Pakistan as a whole. Keywords: Sectarian violence, Kurram District, tribal councils, military interventions, cross-border militancy, extremist financing, peacebuilding, interfaith dialogue, media role, educational reforms.